2021
DOI: 10.1186/s40323-021-00200-w
|View full text |Cite
|
Sign up to set email alerts
|

An SPH framework for fluid–solid and contact interaction problems including thermo-mechanical coupling and reversible phase transitions

Abstract: The present work proposes an approach for fluid–solid and contact interaction problems including thermo-mechanical coupling and reversible phase transitions. The solid field is assumed to consist of several arbitrarily-shaped, undeformable but mobile rigid bodies, that are evolved in time individually and allowed to get into mechanical contact with each other. The fluid field generally consists of multiple liquid or gas phases. All fields are spatially discretized using the method of smoothed particle hydrodyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In Section 3.3 first steps towards a high-fidelity melt pool model that explicitly resolves these effects of evaporation and gas dynamics will be presented. Also first steps towards the representation of mobile powder particles in the melt pool model have been made [27]. Figure 7 displays the melt pool dynamics resulting from variant 2.…”
Section: Exemplary Simulation Resultsmentioning
confidence: 99%
“…In Section 3.3 first steps towards a high-fidelity melt pool model that explicitly resolves these effects of evaporation and gas dynamics will be presented. Also first steps towards the representation of mobile powder particles in the melt pool model have been made [27]. Figure 7 displays the melt pool dynamics resulting from variant 2.…”
Section: Exemplary Simulation Resultsmentioning
confidence: 99%
“…Due to their Lagrangian nature, these particle methods are well suited for calculating free surface flows with complex interfacial geometries, such as tsunamis. The recent research has expanded the range of applications to include geomechanical applications [13][14][15], thermal melting problems in solids [16,17], and medical problems [18].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that tracking the movement of rigid bodies is much easier to model using the SPH method, and it is suitable for complex topologies. 31 In 2019, Ye et al investigated the SPH method as a free mesh method for complex fluid flow. They showed that the SPH method for simulating the flow of complex fluids has advantages that include easy modeling of vortices, free surfaces, solid−liquid interactions, turbulent flows, and deformable and moving boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…They also stated that using the SPH method is much more suitable than network-based methods. Their results showed that tracking the movement of rigid bodies is much easier to model using the SPH method, and it is suitable for complex topologies . In 2019, Ye et al investigated the SPH method as a free mesh method for complex fluid flow.…”
Section: Introductionmentioning
confidence: 99%